(untitled) (Fiep Bulletin - online, 2011)
The study consisted of employees of both genders and random aged 20 to 42 years, officials from one Internet provider in the city of Campos dos RJ. We conducted a cross-sectional study with 2 groups tested with the grid type of focused attention, this test applied 3 times at the beginning of the working day at the end of that same day and next day also the end of the experienced. One group was stimulated using the auditory apparatus of light and sound and / or sound. Computerized electronic device called Orion, manufactured by Mindplace composed of sunglasses with four LEDs on the inner surface of each lens, a stereo headset and a PC where the pre-programmed sessions, which used the appropriate section of No 12 to focus attention lasting 10min. Unlike the second, which became the control group. We found statistically significant difference in the sound group (p <0.05) comparing the same with the control group (p> 0.05), in that at no time was given any encouragement. The results suggest that the use of auditory stimulation made by this unit during the working day, leads to increased performance in focus which in turn could promote the improvement of productivity and quality of work in jobs where the main tool is the computer.